Study on Dynamic Load Monitoring of an Enhanced Stress Absorption Layer - Yang, Sanqiang; Li, Pengfei; Guo, Meng; Liao, Songyang; Wu, Haonan (Frontiers in Materials, 2020)
An effective stress absorption layer can reduce the reflection crack. It can help to extend the service life of road. In this research, an enhanced stress absorption layer of slow crack (ESALOSC) is proposed and compared with the ordinary SBS modified asphalt stress absorbing layer. The strain data of two stress absorption layers under different loads, speeds and temperatures are collected by embedding sensors in the road, and the dynamic response laws of the two stress absorption layers under different conditions are analyzed. The results show that the asphalt pavement is a viscoelastic body and the measured results are consistent with the theoretical solution of layered elasticity: both stress absorbing layers are subjected to pressure. According to the comparison between dynamic overload test and static overload test, the strain deviation between the two sections increases from 11.6% of static load to 25.2% of dynamic load (40 km/h). It indicates that the reinforced effect of geogrid is more obvious under dynamic load. By establishing the relationship between vehicle speed and dynamic response, a vehicle speed and dynamic response model for the ESALOSC is proposed. Based on the test data measured at four temperatures, a model of the temperature and dynamic response in the ESALOSC is proposed. The accuracy and effectiveness of the two models are verified by comparing with other experimental results. The ESALOSC is of great significance for improving the crack resistance of road. The research results provide technical support and theoretical model for the development of long-life pavement in China.